Globalizations and bank performance in China - Sufian, Fadzlan; Habibullah, Muzafar Shah (Elsevier, 2012)
The paper provides for the first time empirical evidence on the impact of economic globalization on the performance of banks operating in the Chinese banking sector. The empirical findings from this study suggest that the well capitalized banks tend to be more profitable, while expense preference behavior exerts negative impact on bank profitability in China. By examining different components of economic globalization, we find that greater economic integration via higher trade flows, cultural proximity, and greater political globalization have significant and positive influence on bank profitability levels. The impacts of personal contacts and information flows seem to work in favour of the Chinese banks. During the period under study, the empirical findings seem to suggest that liberalization (restrictions) of the capital account exerts positive (negative) influence on the profitability of banks operating in the Chinese banking sector.